EFFECTS OF KAOLIN CONCENTRATION AS FILLER ON VULCANIZATION OF RUBBER YARNS - Shinta Marito Siregar (FISITEK: Jurnal Ilmu Fisika dan Teknologi, 2017)
Abstract. A study has been conducted by mixing kaolin and titanium dioxide (TiO2) used as a filler on latex compounds which have been concentrated in the manufacture of rubber yarns with kaolin variations of 0; 6; 12; 15. This research was conducted to find out the result of kaolin concentration effects on rubber yarns vulcanization. The results showed that the concentration of kaolin mixed with titanium dioxide (TiO2) affect on rubber yarns vulcanization. The higher the concentration kaolin the smaller the swelling, so the time of vulcanization will take longer.Keywords: Kaolin, Rubber Yarns, and Vulcanization